Effects of Dietary Phenylalanine and Tyrosine Supplements on the Chronic Stress Response in the Seabream (Sparus aurata) - Salamanca, Natalia; Moreno, Oscar; Giráldez, Inmaculada; Morales, Emilio; de la Rosa, Ignacio; Herrera, Marcelino (Frontiers in Physiology, 2022)
The increase of aquaculture production is associated with a growing interest in improving physiological 13 status and welfare in fish. For this reason, the search for strategies for mitigating stress has been 14 intensified, one of these strategies being food supplementation with different amino acids. The 15 objective of this study was to evaluate the effects of dietary phenylalanine (Phe) and tyrosine (Tyr) 16 supplements on the endocrine and physiological state of seabreams (Sparus aurata) subjected to 17 chronic stress. The fish were stocked at 30 fish / tank in a recirculation aquatic system (RAS), fed one 18 control diet and two diets supplemented with 5% Phe or Tyr for 90 days. Blood was drawn from 10 19 fish per tank every 30 days and weight and length were measured every 15 days. At the end of the 20 experiment, the fish were length/weight measured, and sacrificed for the extraction of blood, head 21 kidney, liver and brain. Classic plasma stress markers (glucose, lactate, proteins, cortisol), as well as 22 hormones derived from Phe and Tyr (adrenaline, norepinephrine and dopamine) and accumulation of 23 amino acids were analyzed. Fish fed diets supplemented with Phe or Tyr showed a reduction in various 24 stress markers and physiological parameters. In addition, the stress condition favored a mobilization 25 of amino acids towards the tissues, especially in supplemented diets, so this excess of amino acids 26 could be used as an energy substrate to cope with stress.